Profil Peternakan Ayam Kampung di Nagari Muaro, Kecamatan Sijunjung, Kabupaten Sijunjung: Profil ayam kampung - Hera Dwi Triani; Afrini Dona; Khairun Nikmah; Fadilla Meidita (Program Studi peternakan, 2022)
Free-range chickens have several advantages over purebred chickens, namely their maintenance is relatively easier, has a stronger immune system. The people in Nagari Muaro work more as ASN and traders so that the level of economy and knowledge of the community is better. This is a supporting factor for the development of free-range chicken livestock in Nagari Muaro. In the development of free-range chicken in Nagari Muaro, the profile of free-range chicken farming is needed as a reference for both the government and the local community. This research is a survey research that uses primary data and secondary data. The data obtained in the form of tabulation (percentages and numbers) and sentence statement, the results of data processing in descriptive, qualitative and quantitative analysis. Based on the results showed that there 1598 of free-range chickenspopulation in Nagari Muaro. Characteristics of chicken farmers in Nagari Muaro average productive age (85.71 %), with the same male and female (50 %). The level of education in general is high school / equivalent (42.86 %) with experience raising livestock for more than 10 years (50 %) and semi-intensive maintenance system (90.48 %). In the rearing management of chicks used are local chicks (33.33 %) and chicks from crosses (66.67 %).. From the research it can be concluded that the characteristics of the average chicken farmer productive age, male and female. The feed does not yet meet the nutritional standards, treatment or prevention of existing diseases. Free-range chickens are generally marketed at collectors.